Preparation of redispersible dry nanoemulsion using chitosan-octenyl succinic anhydride starch polyelectrolyte complex as stabilizer - Kun Sodalee (2022)
In this study, chitosan-octenyl succinic anhydride (OSA) starch polyelectrolyte complex (PEC) was investigated as a stabilizer for redispersible dry nanoemulsion. Fenofibrate, a BCS class II lipid-lowering drug, with poor solubility was used as model drug. The dry nanoemulsions were prepared by spray drying of the formulation consisting of fenofibrate nanoemulsions with chitosan-OSA starch PEC as a stabilizer and lactose as a solid carrier. The effect of formulation variables such as type of emulsion stabilizer, starch to oil ratio, PEC formation method, and lactose amount were investigated. The results showed that the droplet size of liquid nanoemulsions remarkably decreased with an increasing starch to oil ratio. Solid-state characterizations (FTIR, Raman, DSC, and PXRD) revealed that fenofibrate was present in molecularly dispersed form in the spray-dried nanoemulsions. Higher lactose levels provided the spray-dried nanoemulsions with improved redispersibility and smaller droplet sizes. Interestingly, the high drug dissolution without pH effect was obtained at a high lactose level and a high molar charge ratio of chitosan- OSA starch PEC. These results revealed that the redispersible dry nanoemulsion prepared by spray drying could be utilized for improving the dissolution of fenofibrate. Therefore, chitosan-OSA starch PEC was a promising stabilizer for dry nanoemulsion.